The expanded usul of violence by ISIS, Al-Qaeda, and other similar extremist groups - Suleiman, Omar; Akhmetova, Elmira (IAIS Malaysia, 2020)
This paper discusses the methodology of violence used by modern extremist groups that affiliate themselves with Islam, particularly al-Qaeda and ISIS. With the rise of groups claiming to wage jihad, the public has a difficult time discerning traditional concepts from modern aberrations. Furthermore, the groups themselves seem to be alike. The examination of the legal framework used by these groups to justify their violent practices shows a dishonest usage of the traditions they claim to defend. This becomes most obvious with the rise of ISIS, which claims to manifest concepts beyond jihad, such as bay’ah and jizyah. It is also highlighted in the paper that the selective readings of these groups take the most violent interpretations of numerous issues and reduces every target to a disbeliever worthy of being killed or subjugated. By discrediting their usul (interpretive principles), the claims they make for an entire tradition are called into question